Exploring the impact of shared cognitive and emotional factors in career decision-making among adolescents through qualitative inquiry - Fatimah Khakwani; Fatima Khurram; Samar Fahd (Journal of Management Practices, Humanities and Social Sciences, 2022)
Along with other skills, an adolescent need to develop adequate decision-making skills as several important decisions that will have an impact on their future will be taken during this period. One such important decision that needs to be taken is regarding academic and career choices. Most of these choices are influenced by cognitive factors or emotional factors. Keeping in view the prior research gaps, the aim of this paper is to explore the shared cognitive and emotional factors influencing adolescents career choices living in small city. In depth interviews were taken from ten higher secondary school students studying at different colleges in Multan through a convenient sampling technique. Data were analyzed with the help of thematic analysis. Semantic and inductive approach was used to generate themes. Results of the study revealed the autonomy in career choice, stigmas attached with the career choice, individual factors in career choice, and impact of the program on mental and emotional health. It was observed that male students were given a choice in terms of their career as compared to females. Also, male students were more confident and stress-lived as they opted for their desired careers. On the contrary female students feel depressed, helpless and reported emotional and mental health issues due to the unavailability of career choices and forced career on them. The study helped in understanding the impact of program of the study on students cognitive and emotional health. It can be implied from the present study that gender differences still prevail in our education system. Due to scarcity of career options available and the pressure to get admission from the parents in prestigious institutes are making adolescents compromise on their mental and emotional health. Therefore, a career guidance plan should be introduced in education policy for adolescents' mental health. Also, it was also the first study which supported the concept of shared cognitive and emotional experiences.